21st century education technologies for engineers and IT professionals - Chan, Chang Tik (Information Science Reference (an imprint of IGI Global), 2012)
The word technology is inaccurately linked to hardware or tools only, and this misunderstanding has resulted in large sum of money invested in hardware or tools. In consequence, institutions and companies do not get the expected returns from these investments. One of the possible reasons for this could be the lack in understanding and knowledge of software and technology. This chapter attempts to describe the various education technologies in the forms of hardware or tools as well as software which include teaching and learning methods and how they are blended together to achieve effective communications. The technologies described in this chapter are blended learning, podcast, reciprocal peer tutoring, and personal learning environment. Finally, the chapter outlines some future research directions in the area of education technologies.